Timing matters: diurnal spine length variation in pediatric patients during radiotherapy - Karin M. Meijer; Irma W.E.M. van Dijk; Tamara J. Schonk; Brian V. Balgobind; Anna Loginova; Niek van Wieringen; Arjan Bel (Radiation Oncology)
Abstract Background During the day-night cycle, gravity and applied stress to the body mass and spine causes a decrease in body height, which is restored overnight. This diurnal spine length variation has not yet been quantified during radiotherapy. Therefore, we aimed to quantify diurnal spine length variation on cone beam CTs (CBCTs) of pediatric patients (< 18 years) who underwent radiotherapy. Methods For this retrospective study, we included 32 patients (mean age 10.0, range 2.7–16.1 years) who received image guided radiotherapy between 2012 and 2018 in two institutes. Patients were included when they had two fractions per day, or when fractions were scheduled on varying time slots over the course of treatment. Daily CBCTs were registered to the planning CTs using two automatic registrations relative to the bony anatomy; one to vertebra T11 and one to vertebra L4. For each CBCT, the differences between the cranial-caudal (CC) position of the T11 and L4 vertebrae were calculated. To determine the diurnal spine length variation, the difference in vertebrae position between the morning and afternoon CBCTs was calculated. Furthermore, we investigated the possible correlation of diurnal spine length variation with the time slot differences (time interval) between CBCTs (Spearman’s ρ). Results Overall, the median spine length variation was -1.0 (range -3.9–0.1) mm, and we found a significant reduction in spine length over the day (p < 0.001) with substantial variations between patients. Time intervals between CBCTs ranging from 4.0 to 9.5 h were not correlated with spine length reduction (ρ=-0.01; p = 0.95). Conclusions We found a small but significant reduction in spine length (vertebrae T11 to L4) over the course of day in pediatric patients undergoing radiotherapy, measured on CBCT imaging. Spine length reduction did not correlate with CBCT time intervals. However, our results indicate that diurnal spine length reduction could induce a setup error during treatment, and therefore should be considered in pediatric radiotherapy.